Distribusi Dana Filantropi Islam Sebagai Solusi Pengembangan Literasi Digital Dalam Bidang Dakwah - nurbaiti bahrudin; ahmad irfan; rahmah ningsih (Journal of Islamic Philanthropy and Disaster (JOIPAD), 2023)
The COVID-19 pandemic has forced us to live digitally. Therefore, the need for digital literacy is an important needs for the Muslim generation today. Moreover, for those who contribute to educating the society, such as da'i or pendakwah. However, not all of them have digital literacy skills. it is because of the inability to get digital literacy facilities. According to the description, the development of digital literacy can be one of the distribution programs Islamic philanthropy. The research method used in this research is descriptive qualitative using content analysis techniques (content analysis) and library research (library studies). The results of this study inform that the development of digital literacy for the needs of the da'wah can be empowered through Islamic philanthropic funds. If it is related to the group of recipients of the distribution of philanthropic funds in Islam, according to the author, this problem is included in the category of the fi sabilillah. People who struggle in the way of Allah in the form of da'wah activities. Thus, Islamic philanthropy is able to be a solution for the society, especially for the needs of the da'wah.